A THEORETICAL ASPECT OF SOCIAL ENTREPRENEURSHIP - ARPUTHARAJ, R. (International Journal of Psychosocial Rehabilitation, 2020)
Social Entrepreneurship is the unique concept of entrepreneurship which is determined by the problems of society. Social Entrepreneurship offers new ideas to the businesses in respect of social and environment. A social entrepreneur is plays a vital role in taking up a burning societal trouble and meet up it with a modern path. Their main aim is to serve the society and earning profit is the secondary one. This paper examines a theoretical view of social entrepreneurship and the SWOT analysis.